FAKTOR – FAKTOR YANG MEMPENGARUHI WUS TIDAK MENGUNAKAN IMPLAN DAN IUD DI DESA MUKTILINCIR KECAMATAN KOTA BAHARU KABUPATEN ACEH SINGKIL - Mestika Lumbantoruan; Ester Saripati Harianja; Kairina Berutu (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2020)
ABSTRACTAccording to the World Health Organization (WHO) (2014) the use of contraceptives has increased in many parts of the world, especially in Asia and Latin America and the lowest in sub-Saharan Africa. Low interest against the use of IUD acceptors and implants can be influenced by various factors. To find out the factors that influence the WUS didn't use implants and IUD in the village of Mukti Lincir sub-district of Kota Baharu Aceh Singkil 2018. Type of this research is quantitative research is a descriptive with Cross Sectional design. The population of this research is the whole fertile age couples who do not become acceptors KB. The sample in this research is the Foundation of the entire population samples (total sampling). Results of the research there is a majority of the respondents less knowledge as much as 62.2%, majority of respondents negative attitudes as much as 80%, the majority of the positive partner respondents support as much as 88.9%, the majority of health workers and support the positive as much as 95.6% . The conclusion of the results of the research there is the influence of the knowledge of the use of Implants And IUD in the village of Mukti Lincir sub-district of Kota Baharu  Aceh Singkil 2018 P-value 0,000 ( 0.05), there is the influence of attitude towards the use of Implants And IUD in the village of Mukti Lincir sub-district of Kota Baharu Aceh Singkil 2018 P-value  0,043 ( 0.05), there is no influence of the support the couple against the use of the implant And IUD in the village of Mukti Lincir sub-district of Kota Baharu Aceh Singkil 2018 with the value of the P value 0721 ( 0.05), and there is no health officer support influence against the use of the implant And IUD in the village of Mukti Lincir sub-district of Kota Baharu Aceh Singkil 2018 P-value  0,827 ( 0.05). Expect can affect or increase the knowledge about the importance of the use of contraceptives to child birth and distanced restricts the number of children. Keywords: fertile women, implants, IUD